Correlation between circulating myeloid-derived suppressor cells and Th17 cells in esophageal cancer - Jiao, Zhi-Jun (World journal of gastroenterology : WJG, 2012)
AIM： To perform a comprehensive investigation into the potential correlation between circulating myeloidderived suppressor cells （MDSCs） and Th17 cells in esophageal cancer （ECA）. METHODS： A total of 31 patients newly diagnosed with ECA and 26 healthy subjects were included in the current study. The frequencies of MDSCs and Th17 cells in peripheral blood were determined by flow cytometry. The mRNA expression of cytokines, arginase 1 （Arg1） and inducible NO synthase （iNOS） in peripheral blood mononuclear cells （PBMCs） and plasma Arg1 were assessed by real-time polymerase chain reaction and enzyme-linked immunosorbent assay, respectively. RESULTS： There was an increased prevalence of MDSCs in the peripheral blood from ECA patients （15.21% ± 2.25%） when compared with healthy control （HC） （1.10% ± 0.12%, P 〈 0.0001）. The plasma levels of Arg1 in ECA patients were significantly higher than those in HC （28.28 ± 4.10 ng/mL vs 9.57 ± 1.51 ng/ mL, P=0.0003）. iNOS mRNA levels in the peripheral blood of ECA patients also showed a threefold increase compared with HC （P=0.0162）. The frequencies of Th17 cells （CD4 ＋ IL-17A ＋ ） were significantly elevated in ECA patients versus HC （3.50% ± 0.33% vs 1.82% ± 0.19%, P=0.0001）. Increased mRNA expression of IL-17 and ROR-γt was also observed in ECA patients compared with HC （P=0.0041 and P=0.0004, respectively）, while the mRNA expression of IL-6 and tumor necrosis factor-α （TNF-α） showed significant decreases （P=0.0049 and P 〈 0.0001, respectively）. No obvious correlations were found between the frequencies of MDSCs and Th17 cells in the peripheral blood from ECA patients（r=-0.1725, P=0.3534）. Arg1 mRNA levels were positively correlated with levels of IL-6 （r=0.6404, P=0.0031） and TNF-α （r=0.7646, P=0.0001）. Similarly, iNOS mRNA levels were also positively correlated with levels of IL-6 （r=0.6782, P=0.0007） and TNF-α （r=0.7633, P 〈 0.0001）. CONCLUSION： This study reveals the relationship between circulating MDSCs and Th17 cells, which may lead to new immunotherapy approaches for ECA based on the associated metabolites and cytokines.